Width effect and local transient heat transfer characteristics for helium gas flowing over a twisted plate. Issue 2 (1st February 2016) - Liu, Qiusheng; Zhao, Zhou; Fukuda, Katsuya
Abstract : Forced convection transient heat transfer for helium gas at various periods of exponential increase of heat input to a short twisted plate with various helix angles was experimentally studied. Twisted plates were made of platinum plate with a thickness of 0.1 mm and width of 2 and 4 mm. The heat generation rates of the heater was raised with exponential function, Q ˙ = Q 0 exp ( t / τ ), where t is time, and τ is period of heat generation rate. The transient heat transfer experimental data were measured for the periods ranged from 80 ms to 17 s and at a gas temperature of 303 K under 500 kPa. The flow velocities ranged from 4 to 10 m/s. In the experiments, the twisted plates with different width were tested. The local mean heat transfer coefficients have been tested as well. An enhancement in the heat transfer coefficient for the twisted plate with different width was clarified. And also, the heat transfer coefficients for the first half pitch are 24% higher than that for the total length of the same twisted plate.